The Symbolism of the Skull in Vanitas: Homo Bulla Est - Cheney, Liana De Girolami (Cultural and religious studies, 2018)
In Dutch vanitas imagery of Homo bulla est there is a sad child (homo) holding a scalloped shell filled with soap and water. Although the child is amused and playing with the formation of beautiful transparent water circles, his expression is mischievous and melancholic. Blooming flowers and dead trees, burning urns, and cloudy landscapes also accompany this gloomy imagery, which alludes to a warning about moral behavior. The first part of this essay deals with a brief history about the symbolism of the skull in vanitas imagery (1590-1630). And the second part of the essay focuses on two prints by the Dutch artist and printmaker from Haarlem, Hendrick Goltzius (1558-1617), who honored this proverb Homo bulla est in Allegory of Transience as a remembrance of the brevity of life.